The Power of presence: the ‘Cradle to Grave’ installation at the British Museum - Mordhorst, Camilla (Museum and Society, 2015)
The Living and Dying gallery opened at the British Museum five years ago. Praised by critics, this award-winning exhibition is one of the most well attended exhibitions at the Museum. A visit to the gallery makes it apparent that it is the contemporary art installation, Cradle to Grave, that is particularly attractive to the visitors. The aim of this article is to explore why this installation is so effective. However, rather than evaluating visitor responses to the installation, this article analyses the fundamental premises that make it so successful. Using three different theories of ‘proximity’, ‘presence’ and ‘flow of materials’ I thereby attempt a deeper understanding of the installation’s particular intensity. Thus, this article presents a type of exhibition analysis that tries to incorporate the ‘meaning production’ potential of an exhibition, i.e., what an exhibition tells, along with the exhibition’s capability to produce ‘presence’ and ‘material grounding’, i.e., what it does.